Fontes de óleos para juvenis de tambaqui (Colossoma macropomum) exposto ao estresse pelo frio - Fabiano, Karla Larissa Nascimento (2022)
Fish oil (OP) is an expensive and finite source used in fish nutrition. There is a need to replace it with more sustainable sources without harmful effects on fish growth and survival. Tambaqui is an omnivorous freshwater fish that occurs in the Amazon River, adapted to higher water temperatures and with low resistance to cold, being the most produced species in the Amazon region and the second most produced in Brazil. Exposure to rising or falling water temperatures has been reported to elevate levels of lipid oxidative stress biomarkers and create different patterns of antioxidant enzyme response in fish. The present study aims to clarify the effect of different vegetable oil sources on plasma cortisol and oxidative status in juvenile tambaqui (Colossoma macropomum) under cold challenge. A total of 180 fish were used, which were randomly distributed into 18 in thermoregulated tanks (28.0 ± 0.41 ° C), each tank contained 10 fish each (average initial weight of 42.8 ± 0.9 g). Three diets were formulated with different sources of oil: a diet with fish oil (OP) and two diets with vegetable oils (linseed oil - OL and corn oil - OM) and offered during a period of 49 days. At the end of the 7 weeks, the fish were counted and weighed after a 24-hour fast. Fish were randomly selected to sample homeostasis (H). Subsequently, the remaining fish were kept in a tank for a week to proceed with the cold challenge. The temperature was reduced from 28°C to 21°C in 40 minutes. Two experimental samples were performed after the challenge, collections were performed at 3 hours (3H) and 24 hours (24H) after reaching the temperature. The oil sources used in this work did not affect growth, pathological signs and mortality, suggesting that they may be good sources of lipids in the diets of the species studied. As for the dietary effects of the oil source on plasma and morphometric parameters, it was found that they were affected by diet and HPD, except for IHS, which was changed only by HPD. After 24 hrs, the 3 diets showed a reduction in the condition factor, probably in response to the stress challenge. The IHS was altered by the cold, as the animal used glycogen in the stress responses. And for that reason also the animal reduces the condition factor. These changes were presented after 24 hrs. As for the effects of dietary oil source on hepatic antioxidant markers, it was found that, except for GPX, there was a significant interaction between diets and HPD in the activities of all enzymes. These results may be related to the n-3/n-6 balance of the diets where the animals were either more vulnerable and the immune and physiological systems more fragile (OM) or showed a better response to the stressor also due to the n-3 relationship. /n-6 (OP/OL). Considering also that the reduction of temperature can cause a decrease in the activity of the organism that can be intensified if the animal does not present good conditions to react to this stress. In this study, it was verified that the vegetable oil (VO) that presented the best results was OL due to its n-3/n-6 balance, enabling Tambaqui to have a better performance and a better response to the stress factor.